2018
DOI: 10.1371/journal.pntd.0006422
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the pharmacological treatment of human cystic and alveolar echinococcosis: Compounds and therapeutic targets

Abstract: Human cystic and alveolar echinococcosis are helmintic zoonotic diseases caused by infections with the larval stages of the cestode parasites Echinococcus granulosus and E. multilocularis, respectively. Both diseases are progressive and chronic, and often fatal if left unattended for E. multilocularis. As a treatment approach, chemotherapy against these orphan and neglected diseases has been available for more than 40 years. However, drug options were limited to the benzimidazoles albendazole and mebendazole, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 200 publications
(358 reference statements)
0
96
0
3
Order By: Relevance
“…Systemic anti-infective treatment relies on continuous administration of 2 benzimidazole carbamates, ABZ and mebendazole, which are the only anti-infective drugs clinically efficient to interrupt larval growth of Echinococcus spp. (177,178). Mebendazole was the first benzimidazole that was proven efficient for the treatment of echinococcosis (179,180).…”
Section: Treatment Of Cementioning
confidence: 99%
“…Systemic anti-infective treatment relies on continuous administration of 2 benzimidazole carbamates, ABZ and mebendazole, which are the only anti-infective drugs clinically efficient to interrupt larval growth of Echinococcus spp. (177,178). Mebendazole was the first benzimidazole that was proven efficient for the treatment of echinococcosis (179,180).…”
Section: Treatment Of Cementioning
confidence: 99%
“…• BMZ analogs like fenbendazole, flubendazole, oxfendazole, and triclabendazole have been evaluated in the last years, in vitro and in vivo studies (animal models), but did not provide superior efficacy compared to mebendazole or albendazole [57].…”
Section: The Current State Of Knowledgementioning
confidence: 99%
“…Hence, none of the candidate alternative drugs or compounds tested against in vitro or in vivo models of Echinococcus spp. were first designed for the treatment of CE and AE (Siles-Lucas et al, 2018). For decades, most studies have focused on BMZ and new formulations to improve solubility or on the repurposing of clinical drugs (antitumour, antiviral, and antibiotic drugs; Siles-Lucas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…were first designed for the treatment of CE and AE (Siles-Lucas et al, 2018). For decades, most studies have focused on BMZ and new formulations to improve solubility or on the repurposing of clinical drugs (antitumour, antiviral, and antibiotic drugs; Siles-Lucas et al, 2018). Among the developed compounds, a limited number of drugs (isoprinosine Sarciron et al, 1992, mefloquine Rufener et al, 2018, tamoxifen Nicolao et al, 2014 have been shown to be effective in infected animal models.…”
Section: Introductionmentioning
confidence: 99%